PENGEMBANGAN MODEL KESELAMATAN UNTUK PENYEBERANGAN JALAN KOTA BANDUNG (STUDI KASUS SIMPANG BERSINYAL) - Istiqomah Nurhidayati; Aine Kusumawati; Sri Hendarto (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
Traffic crashes are the 10th main cause of death in Bandung. Pedestrians are road users who are more vulnerable to crashes. Pedestrian crashes often occur at intersections as diverseroad users move in the same road space, thus making interaction between road users more complex. Currently, pedestrian safety at intersection is still very low, so it is important to do a study to reduce the number of pedestrian crashes. A model that has been developed by FHWA (Federal Highway Adminstration) for pedestrian safety at intersection is PedISI (Pedestrian Intersection Safety Index). This model can be used to determine which intersections need to be addressed before a crash occurs based on PedISI values. PedISI values show the level of pedestrian safety at intersection. This thesis develops Pedestrian Intersection Safety Index (PedISI) model for signalized intersection in Bandung. The data used consist of pedestrian crashes data, intersection characteristic data, behavioral(conflicts) data and safety rating data. Data were collected from 16 signalized intersections of types 8/2 D, 6/2 D, 4/2 D, 4/2 UD and 2/2 UD. PedISI model formed for signalized intersection in Bandung is PedISI = 3,184 + 0,032THRULNS - 0,005MEDIAN + 0,001SPEED85th with R2 = 0,525. PedISI values for signalized intersections in Bandung based on the model is 3,24 ? 3,45. The average value of PedISI is 3,35 with a standard deviation of 0,06. This model is able to describe the safety conditions of intersection though it has small variation in PedISI values. This is due to the results of surveys that indicated uniformity in respondents perceptions of safety rating values. Thus, it is necessary to improve the safety data collection techniques to obtain a better model.